Material Background of Vedic Warfare - Sharma, R. S.
Besprechungsartikel von Sar va Daman Singh, Ancient Indian Warfare with Special Reference to the Vedic Period (Leiden 1965, E. J. Brill); 304-305 auch zu Harappan weapons.